Respuesta :
42=−2d+6
Flip the equation.
−2d+6=42
Subtract 6 from both sides.
−2d+6−6=42−6
−2d=36
Divide both sides by -2.
−2d/−2 = 36/−2
d=−18
Flip the equation.
−2d+6=42
Subtract 6 from both sides.
−2d+6−6=42−6
−2d=36
Divide both sides by -2.
−2d/−2 = 36/−2
d=−18
-2d+6=42
ok first you will take 6 and subtract it from 6 and take 42 and subtract 6
-2d+6-6=42-6
-2d=36
Now you divide -2/-2 and 36/-2
d=-18
because positive and a negative divided is a negative
ok first you will take 6 and subtract it from 6 and take 42 and subtract 6
-2d+6-6=42-6
-2d=36
Now you divide -2/-2 and 36/-2
d=-18
because positive and a negative divided is a negative